2001
DOI: 10.1159/000046879
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Regulation of Mitochondrial Superoxide Generation

Abstract: The mitochondrion is the greatest source, as well as the target, of reactive oxygen species (ROS). Increasing evidence indicates that vitamin E can act as a biological modifier independently of its antioxidant activity. Experimental evidence available shows that vitamin E is capable of dose-dependently regulating mitochondrial generation of superoxide and hydrogen peroxide. Vitamin E may modulate mitochondrial production and levels of superoxide by preventing electron leakage, by mediating the superoxide gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 104 publications
1
27
0
Order By: Relevance
“…Recent studies indicate that Á-tocopherol may be important in prevention of human disease [30]. ·-Tocopherol reacts with superoxide and peroxyl radicals to form ·-tocopheroxyl radical [31]. Reduced coenzyme Q 10 regenerates ·-tocopherol from tocopheroxyl radical, thereby maintaining adequate concentrations of vitamin E [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that Á-tocopherol may be important in prevention of human disease [30]. ·-Tocopherol reacts with superoxide and peroxyl radicals to form ·-tocopheroxyl radical [31]. Reduced coenzyme Q 10 regenerates ·-tocopherol from tocopheroxyl radical, thereby maintaining adequate concentrations of vitamin E [32].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the rate of superoxide generation by submitochondrial particles was found to inversely related to the vitamin E content in skeletal muscle, liver, and kidney of mice [44]. These findings suggest that dietary vitamin E may mediate the generation and/or level of superoxide and related ROS/RNS via maintaining mitochondrial integrity and stability, mediating the superoxide generation systems, and/or scavenging superoxide generated [43,45].…”
Section: How May Vitamin E Protect Against Oxi-dative Damage?mentioning
confidence: 76%
“…Hence, insights into the topology of the enzyme in relation to the respiratory chain are crucial for understanding regulatory mechanisms of NO action. It has been reported that 5% of the oxygen consumed by the mitochondrial respiratory chain is converted into superoxide (29). The formed superoxide reacts with NO or could be converted to hydrogen peroxide (catalyzed by Mn-SOD, 10 9 mol/liter Ϫ1 s Ϫ1 ; spontaneously, 10 5 mol/liter Ϫ1 s Ϫ1 ) (30).…”
Section: Discussionmentioning
confidence: 99%